A avaliação educacional em larga escala e as políticas municipais de educação em duas cidades do Estado de São Paulo - Blasis, Eloisa Barbosa de Oliveira De (2011)
The restructuring of the educational system promoted by the Brazilian federal government in the 1990s has inserted new perspectives on the different spheres of the educational management, from the secretariat to the schools themselves. Basically, this reformulation follows three operational axes: evaluation of the teaching systems, political and administrative decentralization, and educational funding. Decentralization has led municipalities to assume and organize basic teaching, while educational assessment was instituted as a control instrument to guarantee educational quality standards in all spheres municipality, state and federal involved, thus redefining political relationships among them. This study explores the effects of large scale educational assessment in formulating local (municipal) educational policies. Two case studies are examined, two municipalities that have assumed basic teaching since 1999 and 2001 respectively, aiming to capture a fresh perspective of the whole process at the base of the pyramid, by means of interviews with local managers in charge. Data analysis, based on the concept of technological rationality formulated by Herbert Marcuse and others from the Frankfurt School, show that local managers tend to use local evaluation results to promote administrative measures for adjusting to expected standards imposed by average indexes produced by large scale educational assessment. These measures are mostly concerned with intervening at the school level, in order to get more functional efficiency